Underestimated Needs for Lymphoma Patients: An Assessment Issue: Psychosocial Markers for Haematologic Patients - Miraglia Raineri, Alessandra; Lauro Grotto, Rosapia; Fioravanti, Giulia; Rotella, Francesco; Alterini, Renato; Bosi, Alberto; Faravelli, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. The aim of the current study was to explore under-considered psychosocial needs for lymphoma cancer group. A model of the role of psychosocial factors and Stressful Life Events was operationalized. Method. We used Discriminant Analysis to test predictive power of the model. 103 oncological patients (gender: 42.7 % vs 49.3 % of females 55.2 ±15.6 vs 53.7±14.9) were matched with 140healthy control groups in the study. The following instruments were utilized to conduct the study: the Florence Psychiatric Interview, Hospital Anxiety Depression Scale, Multidimensional Scale of Perceived Social Support, Beck Depression Inventory I, and Sense of Mastery. Results. The model satisfied the assumption criteria and were significant (Ʌ= .665, χ2= 105.83, p< .001).Conclusion.Stressful events, depression and anxiety were adequate markers of the psychological status of lymphoma patients. Our results point out the relevance of taking into account psychosocial factors in hematology